PENGARUH PEMAHAMAN AKUNTANSI, SISTEM PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DAERAHKABUPATEN NAGEKEO - JIlhan Reynaldi Keytimu; Yohana Febiani Angi; Indri H Tiwu (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to determine the effect of accounting understanding, internal control, and information technology utilization on the quality of financial reports. This study was conducted on auditors in the Nagekeo Regency Government. The sampling technique used was saturated sampling, with a sample size of 40 employees. The data analysis techniques used were: first, descriptive statistical tests; second, data quality tests, including validity and reliability tests; third, multiple linear regression tests; fourth, classical assumption tests, including normality tests, multicollinearity tests, and heteroscedasticity tests; and finally, hypothesis tests, including t-tests, F-tests, and coefficient of determination (R2) tests, using the SPSS 26 application program. Accounting understanding, internal control, and information technology utilization influence the quality of financial reports. The results of this study simultaneously indicate that accounting understanding, internal control, and information technology utilization influence the quality of financial reports.